4(2x+3)=7x+4

Simple and best practice solution for 4(2x+3)=7x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+3)=7x+4 equation:


Simplifying
4(2x + 3) = 7x + 4

Reorder the terms:
4(3 + 2x) = 7x + 4
(3 * 4 + 2x * 4) = 7x + 4
(12 + 8x) = 7x + 4

Reorder the terms:
12 + 8x = 4 + 7x

Solving
12 + 8x = 4 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
12 + 8x + -7x = 4 + 7x + -7x

Combine like terms: 8x + -7x = 1x
12 + 1x = 4 + 7x + -7x

Combine like terms: 7x + -7x = 0
12 + 1x = 4 + 0
12 + 1x = 4

Add '-12' to each side of the equation.
12 + -12 + 1x = 4 + -12

Combine like terms: 12 + -12 = 0
0 + 1x = 4 + -12
1x = 4 + -12

Combine like terms: 4 + -12 = -8
1x = -8

Divide each side by '1'.
x = -8

Simplifying
x = -8

See similar equations:

| B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 | | 8(y-5)=6-18 | | .20x+.25+9=.21 | | 4-15y=4 | | -14=(2/5)(9-2b) | | -32=(8/7)(3w-1) | | .80x+.25(60)=.70(x+60) | | c=0.90y+1.65 | | 28s-2=59s-64 | | 9=-9v^2+6v |

Equations solver categories